Characteristics and correlates of seclusion and mechanical restraint measures in a Parisian psychiatric hospital group - Dauriac-Le Masson, Valerie; El-Khoury Lesueur, Fabienne; Lahaye, Justine; Launay, Corinne; Christodoulou, Alexandre; Boiteux, Catherine; Maman, Judith; Bonnemaison, Xavier; Perquier, Florence; Vacheron, Marie-Noelle (Frontiers in Psychiatry, 2024)
Introduction Seclusion or restraint (S/R) are last-resort measures used in psychiatry to ensure the safety of the patient and the staff. However, they have harmful physical and psychological effects on patients, and efforts to limit their use are needed. We describe the characteristics and correlates of S/R events in four Parisian psychiatric centers. Methods Within a 3-month period, November 5, 2018 to February 3, 2019, we recorded data for patients experiencing an S/R measure as well as characteristics of the measures. We studied the mean duration of a S/R event, the time between hospital admission and the occurrence of the event, as well as correlates of these durations. We also examined factors associated with use of a restraint versus a seclusion measure. Results For the 233 patients included, we recorded 217 seclusion measures and 64 mechanical restraints. Seclusion measures mostly occurred after the patient’s transfer from the emergency department. The duration of a seclusion measure was about 10 days. Patients considered resistant to psychotropic treatments more frequently had a longer seclusion duration than others. The mean duration of a mechanical restraint measure was 4 days. Male sex and younger age were associated with experiencing mechanical restraint. Discussion S/R measures mostly occur among patients perceived as resistant to psychotropic drugs who are arriving from the emergency department. Developing specific emergency department protocols might be useful in limiting the use of coercive measures.